INOVASI PELAYANAN PUBLIK MELALUI LAYANAN OKE MASYARAKAT KELILING (LOMAK) DI KECAMATAN RUMBAI BARAT KOTA PEKANBARU - Bella Putri Ayuni; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The mobile community okay service (LOMAK) is a sub-district integrated administration service that is deployed to serve administration in the midst of community settlements. LOMAK's innovation is contained in the Decree of the Rumbai Sub-district of Pekanbaru City Number: Kpts/21.1/KR/VII/2019 concerning the Innovation of the Mobile Community Okay Service (LOMAK). The word LOMAK in Malay is usually interpreted as delicious, the Rumbai sub-district government hopes that this innovation is as the name suggests, good for the community and good for the government. Rumbai District. The purpose of this study is to find out how to innovate public services through the mobile community okay service and to find out the supporting and inhibiting factors for the success of mobile community okay service innovation. This study uses a purposive sampling technique with qualitative research using a descriptive approach and the required data, both primary and secondary data obtained through observation, interviews, and documentation, are then analyzed based on the research problem. The results of this study indicate that: first, the innovation of public services through the mobile community okay service in the Rumbai sub-district, Pekanbaru city has not run optimally. Second, the factors that support the success of mobile community service innovation are motivation and increased community participation. The inhibiting factors are the Covid-19 pandemic, and the change in the name and number of villages in the West Rumbai sub-district.  Keywords :Innovation, Public Service